STRATEGI PEMBELAJARAN SMART SOLUTION DAN REMEDIAL ENRICHMENT CONSULTING UNTUK MENINGKATKAN MOTIVASI BELAJAR DI MIN KOTA BIMA - Carolina, Destri; Syarifuddin; Anhar, Ade S (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Learning motivation is an important factor in students' academic success. This study aims to analyze the effectiveness of Smart Solution and Remedial Enrichment Consulting learning strategies in improving learning motivation of fifth grade students of MIN Kota Bima. The research method used is qualitative with a descriptive approach. Data collection was carried out through observation, interviews, and documentation with teachers and students. The results of the study indicate that the Smart Solution learning strategy is able to improve students' understanding through a problem-solving-based approach. Meanwhile, the Remedial Enrichment Consulting strategy provides opportunities for students with learning difficulties to obtain additional guidance systematically, so that they can catch up and increase their confidence in learning. Thus, the implementation of Smart Solution and Remedial Enrichment Consulting strategies can be an effective solution in improving students' motivation and learning outcomes.